2019
DOI: 10.1002/hep.30882
|View full text |Cite
|
Sign up to set email alerts
|

Six‐Transmembrane Epithelial Antigen of the Prostate 3 Deficiency in Hepatocytes Protects the Liver Against Ischemia‐Reperfusion Injury by Suppressing Transforming Growth Factor‐β‐Activated Kinase 1

Abstract: Background and Aims Hepatic ischemia‐reperfusion (I/R) injury remains a major challenge affecting the morbidity and mortality of liver transplantation. Effective strategies to improve liver function after hepatic I/R injury are limited. Six‐transmembrane epithelial antigen of the prostate 3 (Steap3), a key regulator of iron uptake, was reported to be involved in immunity and apoptotic processes in various cell types. However, the role of Steap3 in hepatic I/R‐induced liver damage remains largely unclear. Appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 43 publications
3
46
0
Order By: Relevance
“…Furthermore, the MAPK signaling pathway has also been reported to have an important role in the control of hepatic IRI [ 25 , 30 ]. Among the MAPK family members, MAPK/ERK kinase (MEK) and extracellular-signal-regulated kinase (ERK) are known downstream targets of FGF10 [ 10 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the MAPK signaling pathway has also been reported to have an important role in the control of hepatic IRI [ 25 , 30 ]. Among the MAPK family members, MAPK/ERK kinase (MEK) and extracellular-signal-regulated kinase (ERK) are known downstream targets of FGF10 [ 10 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cellular apoptosis directly contributes to liver damage during hepatic IRI [ 18 , 25 , 30 ]. Recent studies demonstrated that FGF10 can inhibit neuronal apoptosis during cerebral IRI [ 31 ], suggesting a possible role for FGF10 in the regulation of apoptosis after liver IRI.…”
Section: Resultsmentioning
confidence: 99%
“…given the essential role of LSECs in the maintenance of liver functioning, insight into the biological role of miR-9-5p in LSCEs is worthwhile. The conventional mouse model of liver I/R injury involves clamping the portal vein, bile duct and hepatic artery with microvascular clips to interrupt the blood supply, followed by reperfusion [22,23]. The method, however, makes it di cult to elucidate cell type-speci c role of the factor studied.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to in ammation, recent evidence indicated that apoptosis is another essential contributor to hepatic I/R injury (Guo et al 2020). Apoptosis can also be enhanced by reperfusion-induced in ammatory responses (Jassem et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Liver ischemia-reperfusion (I/R) injury is a crucial contributor to liver damage and dysfunction after liver transplantation, partial hepatectomy, and hemorrhagic shock (Chen et al 2020). Although great efforts have been made to explore therapeutic strategies to alleviate acute liver I/R injury, no pharmacologic intervention has been documented to be effective in preventing or treating this condition in clinical practice (van Golen et al 2013).…”
Section: Introductionmentioning
confidence: 99%